Peningkatan Minat Belajar Siswa Tingkat Sekolah Dasar melalui Bimbingan Belajar Hybrid Learning di Kelurahan Penjaringan Sari - Sobirudin, Anang Lutfi; Nur, Dhani Ichsanuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the roles of students is to contribute to the community through dedication to realize the Three Pillars of Higher Education. One of the dedication activities is tutoring with the Hybrid Learning method. The goal of this tutoring is to increase students' interest in learning at the Elementary and Kindergarten levels in the Penjaringan Sari Village. The Hybrid Learning method combines face-to-face and virtual learning for more dynamic and diverse interaction between tutoring participants and mentors. This activity involves school students, students as mentors, and the student's parents community. Focusing on increasing interest in learning, the Hybrid Learning tutoring method tries various strategies to increase student engagement, optimize the use of learning technology, and adjust the teaching materials needed. The results of this dedication activity show a significant increase in students' interest in learning, measured through attendance in the learning process, improved subject grades, and positive responses from students and their parents. This dedication activity pays attention to the importance of combining digital technology and conventional learning to achieve more effective learning outcomes at the Elementary level.